Challenges and proposed solutions to conducting Alzheimer’s disease psychosis trials - Ballard, Clive; Tariot, Pierre; Soto-Martin, Maria; Pathak, Sanjeev; Liu, I-Yuan (Frontiers in Psychiatry, 2024)
As of 2023, approximately 6 million Americans have Alzheimer's disease (AD), and that number is projected to grow to 13 million by 2050. A large percentage of those with AD will experience psychosis over the course of their illness, and the incidence of Alzheimer's disease psychosis (ADP) is approximately 10% per year. This high incidence and prevalence of ADP places substantial stress on the aging population as ADP is associated with a significant burden for patients, care partners, and their families. At present there are no approved treatments for ADP, which may be due in part to the considerable challenges of conducting clinical trials for regulatory approval in the ADP indication. This perspective article discusses seven distinct challenges of conducting ADP trials and proposes seven approaches that could help to overcome them. The goal of these solutions is to improve the clinical evaluation of potential ADP therapies, so that future randomized, placebo-controlled trials will be more likely to identify treatments demonstrating safety and efficacy.